Rancang Bangun Aplikasi Penelusuran Kehilangan Perangkat Mobile Berbasis Android - Indra Suwahyono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
In this modern era, android based smart phone widely dominate the world market, especially Indonesia. Not only possessed by the premium class it also used by middle and lower class customer, though sometimes prone to be lost or misplaced somewhere. This study purposed to develop an application that is able to trace the missing android smart phone in order to avoid loss or being hidden unintentionally that possibly put the owner into a very difficult situation, especially if the smart phone or mobile device has moved away from the known missing position. Lost mobile device tracking application, used to trace and discover the position of a lost smart phone. It built using the Java programming language in the Eclipse IDE and the Android SDK software. It also designed using waterfall method, a method that shows a systematic and sequential approach through stages in SDLC (Software Development Life Cycle) and software modeled using UML (Unified Modeling Language). The application active and works by using SMS commands and sent to a friend's phone number that already registered. SMS command 'siren' to ring the alarm, as well as SMS command 'where' to know the latitude and longitude coordinates using GPS assistance to get the map location and Google Maps API to get the route to the location. The entire available features menu in the lost mobile device tracking application has been tested and running normally. Work using SMS commands that ease the users to run the application as long as credits balance available. For further development, this application is expected to control the system remotely so the important data protected and cannot be accessed by the inventor.